Peran Tata Kelola Perusahaan Dalam Meningkatkan Relevansi Nilai Pengukuran Nilai Wajar Aset Nonkeuangan - Pratiwi, Ananta Dian; Tangkau , Jaqueline; Tala, Olifia (Politeknik Negeri Ambon, 2023)
Accounting information is one of many information that is used in making decisions by investors. Accounting information has value relevance when the information raises investor reactions, meaning that the information is used for decision-making that affects stock prices. This study aimed to examine the value relevance of earnings, book value of equity, and fair value measurement of non-financial assets, along with the role of corporate governance in increasing the value relevance of that information. This study used 18 companies listed on the LQ45 index on the Indonesia Stock Exchange (IDX) during 2018-2022. Moderated Regression Analysis (MRA) was used as an analytical tool to test the relationship of research variables. The results showed that earnings, book value of equity, and fair value measurement of nonfinancial assets had value relevance. Corporate governance was found to play a role in improving the value relevance of earnings and the fair value measurement of non-financial assets. The existence of corporate governance was able to reduce agency conflicts and provide assurance that information has been presented fairly to investors thereby increasing value relevance.